108k views
0 votes
Given that f(x)= 4x + 1 and g(x) = 4x+2/3 solve for g(f(0))

User Paul Liang
by
5.7k points

2 Answers

4 votes

Let's compute f(0) first, and then we'll compute g with that input. We have


f(x)=4x+1 \implies f(0)=4\cdot 0+1 = 0+1=1

So, we have


g(f(0))=g(1) = 4\cdot 1+(2)/(3)=4+(2)/(3)=(12)/(3)+(2)/(3)=(14)/(3)

User Rossen
by
6.1k points
3 votes

Answer:

4
(2)/(3)

Explanation:

To evaluate g(f(0)), evaluate f(0) then use this value to evaluate g(x)

f(0) = 4(0) + 1 = 0 + 1 = 1, then

g(1) = 4 +
(2)/(3) = 4
(2)/(3)

User Jon Hanson
by
6.1k points